Pelatihan dan Pendampingan Laporan Pembukuan Keuangan Sederhana Bagi Pelaku UMKM di Desa Argorejo - Maria Yunita Meo; Hasim As`ari (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the national economy, especially in rural areas, contributing significantly to income and job creation for the community. However, the sustainability of MSMEs is often affected by financial management challenges, especially the lack of understanding of proper accounting. Accounting as a tool to compile accurate financial information can actually help improve the financial performance of MSMEs, but is often considered difficult by economic stakeholders. Through this activity, it is hoped that MSME stakeholders will gain better awareness and skills in managing business finances, so that participants gain a deeper understanding of accounting and its impact on business stability and growth, and ongoing support and training can also support MSMEs in adopting more complex accounting methods, increasing their professionalism and competitiveness in the market.